Copper-clad laminate and method for producing the same
Patent Information
- Application Number
- JP2024186658
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-08-29
- Filing Date
- 2024-10-23
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2040-08-07
AI Technical Summary
【0023】 本発明によれば、低誘電フィルムと無電解銅めっき層との界面を粗化することなく高い密着力を確保することが可能となる。
Smart Images

Figure 2025022881000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a copper clad laminate for a flexible circuit board mounted on a communication device or the like, and a method for producing the same. [Background technology]
[0002] In recent years, electronic devices have become increasingly smaller and more powerful, and this is due in large part to the development of communication devices that use radio waves, such as mobile phones and wireless LANs. In particular, with the increasing volume of information, as exemplified by big data generated by the IoT, communication signals between electronic devices are becoming increasingly high-frequency, and the circuit boards mounted on such communication devices require materials with low transmission loss (dielectric loss) in the high-frequency range.
[0003] It is known that the dielectric loss that occurs in this circuit board is proportional to the product of three elements: "signal frequency," "square root of the dielectric constant of the board material," and "dielectric loss tangent." Therefore, to obtain the above-mentioned excellent dielectric properties, a material with as low a dielectric constant and dielectric loss tangent as possible is necessarily required.
[0004] In such circuit boards, the circuits are generally formed of a metal such as copper. The copper layer in the circuit board is formed by, for example, a lamination method as disclosed in Patent Document 1, a casting method as disclosed in Patent Document 2, or a plating method as disclosed in Patent Document 3. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 6202905 [Patent Document 2] Patent No. 5186266 [Patent Document 3] JP 2002-256443 A Summary of the Invention [Problem to be solved by the invention]
[0006] As mentioned above, reducing transmission loss in high-frequency communications has become an important development element in recent years, and resin films with low transmission loss (hereinafter also referred to as "low dielectric films" or "low dielectric resin films") are beginning to be used as base materials for flexible circuit boards. However, the conventional techniques including the above-mentioned patent documents do not ensure sufficient adhesion between the above-mentioned low dielectric film and a metal layer (e.g., a copper layer) for forming a circuit. For example, in the lamination method exemplified in the above-mentioned patent document 1 and the casting method exemplified in the above-mentioned patent document 2, the interface between the copper layer and the low dielectric film must be roughened, which deteriorates the smoothness of the interface and causes transmission loss.
[0007] On the other hand, according to the plating method shown in Patent Document 3, a relatively good adhesion between a resin film with a high dielectric constant and a copper layer can be ensured. However, since a low dielectric film has a relatively rigid molecular structure and has little polarization on the surface, ensuring adhesion was an issue when a copper layer was formed by plating. That is, when a low dielectric film is used as a substrate, a conventional method for ensuring adhesion was widely to roughen the interface, but since there is a trade-off with transmission loss, it was desired to achieve both. Although a sputtering method, for example, can be used as a manufacturing method other than the above, the manufacturing process is more complicated than the above methods, and many problems remain in terms of productivity and cost.
[0008] The present invention aims to solve the above-mentioned problems as an example, and specifically aims to provide a copper-clad laminate and a manufacturing method thereof that can ensure high adhesion while ensuring smoothness to suppress transmission loss at the interface between a low dielectric film serving as a base material and a metal layer for circuit formation. [Means for solving the problem]
[0009] In order to solve the above-mentioned problems, a copper clad laminate in one embodiment of the present invention includes: (1) a low dielectric resin film having a relative dielectric constant of 3.5 or less and a dielectric loss tangent of 0.008 or less at a frequency of 10 GHz; and an electroless copper plating layer laminated on at least one surface of the low dielectric resin film; The electroless copper plating layer is an electroless Cu-Ni alloy plating layer, The low dielectric resin film Cu-Ni alloy The average surface roughness Ra at the interface between the resin film and the plating layer is 1 to 150 nm, and Cu-Ni alloy With plating layer 90° Peel The strength is 4.2N / cm or more. a plating layer side interface of the resin film is provided with hydroxyl groups, and the number of hydroxyl groups at the plating layer side interface is greater than the number of carboxyl groups; and a TOF-SIMS spectrum of the plating layer side interface has a peak intensity of 1000 or more at a mass number of 121. The present invention is characterized in that:
[0010] In the copper clad laminate described in (1) above, (2) the intensity of mass 121 at the interface of the resin film on the plating layer side, measured by time-of-flight mass spectrometry (TOF-SIMS), is preferably 800 or more.
[0011] Also, as mentioned above (1) Or (2) In the copper clad laminate according to any one of the above, 3 The resin film is preferably made of any one of polyimide, modified polyimide, liquid crystal polymer, and fluorine-based resin, or a mixture thereof.
[0012] In addition, the above (1)-( 3 In the copper clad laminate according to any one of the preceding claims, 4 ) The above Electroless Cu-Ni alloy The Ni content in the plating layer is preferably 3 wt % or less.
[0013] In addition, the above (1)-( 4 In the copper clad laminate according to any one of the preceding claims, 5 ) The electroless Cu-Ni alloy The thickness of the plating layer is preferably in the range of 0.1 to 1.0 μm.
[0014] In addition, the above (1)-( 5 In the copper clad laminate according to any one of the preceding claims, 6) The resin film is electrolessly Cu-Ni alloy It is preferable that a metal selected from the group consisting of Cu, Ni, Pd, and Ag is present at the interface on the plating layer side.
[0015] In addition, the above (1)-( 6 In the copper clad laminate according to any one of the preceding claims, 7 ) The electroless Cu-Ni alloy It is preferable that the plated layer further includes a protective layer formed on the plated layer.
[0016] In addition, the above (1)-( 7 In the copper clad laminate according to any one of the preceding claims, 8 ) The electroless Cu-Ni alloy The plating layers are formed on both sides of the resin film, and the resin film has a through hole, and the inner wall of the through hole is provided with the electroless plating. Cu-Ni alloy It is preferable that at least a part of the plating layer is formed.
[0017] In order to further solve the above-mentioned problems, a method for producing a copper clad laminate according to one embodiment of the present invention comprises the steps of: 9 ) A method for producing a copper clad laminate by forming an electroless copper plating layer on a resin film having a relative dielectric constant of 3.5 or less at a frequency of 10 GHz and a dielectric loss tangent of 0.008 or less, the method comprising: a first surface modification step of imparting hydroxyl groups to a surface of the resin film; a second surface modification step of imparting an electric charge to the surface to which the hydroxyl groups have been imparted by a wet method; a catalyst adsorption step of adsorbing a catalyst to the surface to which the electric charge has been imparted; and an electroless copper plating step of adsorbing the surface to which the catalyst has been adsorbed. Cu-Ni alloy An electroless copper plating process for forming a plating layer; Cu-Ni alloy A heating step of heating the copper clad laminate on which the plating layer is formed. In the first surface modification step, a mixture of an alkaline aqueous solution and an amino alcohol is used, and the mixture ratio in the mixture is, in terms of molar ratio, -OH groups and -NH 2 The ratio of groups is (-NH 2 (-OH group / -OH group) = 2.00 to 3.00 , The plating layer side interface of the resin film is provided with the hydroxyl groups, and the number of the hydroxyl groups at the plating layer side interface is greater than the number of the carboxyl groups. It is characterized by the above.
[0018] In order to further solve the above-mentioned problems, a method for producing a copper clad laminate in one embodiment of the present invention is (10) a method for producing a copper clad laminate produced by forming an electroless copper plating layer on a modified polyimide (MPI) as a resin film having a relative dielectric constant of 3.5 or less at a frequency of 10 GHz and a dielectric loss tangent of 0.008 or less, the method comprising: a first surface modification step of imparting carboxyl groups and hydroxyl groups to a surface of the resin film using a mixed solution of an alkaline aqueous solution and an amino alcohol; a second surface modification step of imparting an electric charge to the surface to which the hydroxyl groups have been imparted by a wet method; a catalyst adsorption step of adsorbing a catalyst to the surface to which the electric charge has been imparted; an electroless copper plating step of forming an electroless Cu-Ni alloy plating layer on the surface to which the catalyst has been adsorbed; and a heating step of heating the copper clad laminate on which the electroless Cu-Ni alloy plating layer has been formed, The plating layer side interface of the resin film is provided with the hydroxyl groups, and the number of the hydroxyl groups at the plating layer side interface is greater than the number of the carboxyl groups.
[0019] In addition, 9 ) Or (10) In the method for producing a copper clad laminate according to the present invention, 11 ) The alcohol is preferably aminoethanol.
[0020] In addition, 9 )~( 11 In the method for producing a copper clad laminate according to any one of the above, 12 In the second surface modification step, and It is preferable to adsorb a positive charge to the surface to which hydroxyl groups have been added and then adsorb a negative charge to the surface.
[0021] In addition, 12 In the method for producing a copper clad laminate according to the present invention, 13 It is preferable to add a cationic surfactant to the surface to adsorb the positive charges and an anionic surfactant to the surface to adsorb the negative charges.
[0022] In order to further solve the above-mentioned problems, the flexible circuit board according to one embodiment of the present invention has the above-mentioned (1) to ( 8 ) a circuit is formed using the copper clad laminate according to any one of the preceding claims. Effect of the Invention
[0023] According to the present invention, it is possible to ensure high adhesion without roughening the interface between the low dielectric film and the electroless copper plating layer. [Brief description of the drawings]
[0024] [Figure 1] 1 is a schematic cross-sectional view showing a copper clad laminate 10 of the present embodiment. [Diagram 2] 1 is a schematic diagram showing the state of the interface between a resin film 1 and an electroless copper plating layer in a copper clad laminate 10 of the present embodiment. [Diagram 3]2 is a schematic diagram showing a through-hole H in the copper clad laminate 10 of the present embodiment. FIG. [Figure 4] 1 is a diagram showing a flow of a method for manufacturing a copper clad laminate 10 of the present embodiment. [Diagram 5] 1 is a schematic cross-sectional view showing a copper clad laminate 20 of the present embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0025] Hereinafter, a copper clad laminate 10 of this embodiment will be described with reference to FIG. <Copper clad laminate> The copper clad laminate 10 according to this embodiment has a resin film 1 serving as a substrate, and an electroless copper plating layer 2 laminated on at least one surface of the resin film 1. In this embodiment, the resin film 1 serving as the substrate is preferably a so-called low dielectric resin film that has excellent electrical properties in the high frequency range. Specifically, films of known liquid crystal polymers, fluorine-based resins, polyimide resins, modified polyimide resins, epoxy resins, polytetrafluoroethylene resins, polyphenylene ether resins, and the like, each of which has a lower dielectric loss, are preferably used. These resins may be monopolymers or copolymers. In addition, the resins may be used alone or as a composite obtained by blending a plurality of resins.
[0026] Specifically, the electrical properties of the resin film 1 serving as the base material are preferably such that the relative dielectric constant at a frequency of 10 GHz is 3.5 or less and the dielectric loss tangent is 0.008 or less. The thickness of the resin film 1 is not particularly limited, but in practice it is preferably 5 μm to 100 μm.
[0027] Next, the electroless copper plating layer 2 laminated on at least one surface of the resin film 1 will be described. In this embodiment, the electroless copper plating layer 2 is preferably formed by electroless copper plating. That is, since the resin film 1 has insulating properties, the copper plating layer is formed by electroless plating. Note that this electroless copper plating layer 2 may serve as a seed layer when manufacturing a flexible circuit board by a semi-additive method (SAP method or MSAP method), a subtractive method, a full additive method, or the like.
[0028] In this embodiment, the electroless copper plating layer 2 may be a plating of Cu alone or a copper alloy plating containing a predetermined amount or more of copper. Examples of the copper alloy include a Cu-Ni alloy, a Cu-Zn alloy, and a Cu-Sn alloy.
[0029] When the electroless copper plating layer 2 is formed of a Cu-Ni alloy, the Ni content is 3 wt% or less, preferably 0.01 to 3 wt%, more preferably 0.01 to 1.5 wt%, and even more preferably 0.01 to 0.3 wt%. When the electroless copper plating layer 2 is made of a Cu-Ni alloy, it is preferable to include Ni, which has a higher plating deposition rate than Cu, because this suppresses internal stress in the plating layer and therefore suppresses blistering. On the other hand, if the amount of Ni in the Cu-Ni alloy exceeds 3 wt%, magnetism may occur in the Cu circuit, which may increase transmission loss, and etching may become complicated when forming copper wiring. Therefore, it is preferable that the amount of Ni in the Cu-Ni alloy is 3 wt% or less. Also, if the amount of Ni in the Cu-Ni alloy is less than 0.01 wt%, plating deposition rate deteriorates. The Ni content in the electroless plating layer 2 can be measured by known techniques such as an X-ray fluorescence analyzer (XRF) or an inductively coupled plasma (ICP) analyzer.
[0030] In this embodiment, a known method may be used as the electroless copper plating method for forming the electroless copper plating layer 2 as long as it is possible to form the electroless copper plating layer 2 having a predetermined thickness. The electroless copper plating method will be described in detail in the section on the manufacturing method described later. In this embodiment, the thickness of the electroless copper plating layer 2 is preferably in the range of 0.1 μm to 1.0 μm from the viewpoints of production efficiency and cost.
[0031] If the thickness of the electroless copper plating layer 2 is less than 0.1 μm, it is not preferable because it may not function as a seed layer when manufacturing a flexible circuit board by a semi-additive method, whereas if the thickness of the electroless copper plating layer 2 is more than 1.0 μm, it is not preferable because it may be difficult to form a fine circuit pattern when manufacturing a flexible circuit board.
[0032] The thickness of the electroless copper plating layer 2 is more preferably 0.1 μm to 0.8 μm. This is because, particularly in circuit formation by the SAP method, a shorter etching time (thinner thickness) enables the formation of a finer pattern with less impedance variation in the cross-sectional direction of the circuit.
[0033] In the copper clad laminate 10 of this embodiment, the resin film 1 has an average surface roughness Ra of 1 to 150 nm, preferably 20 to 150 nm, at the plating layer side interface in contact with the electroless copper plating layer 2. In particular, when the resin film 1 is a liquid crystal polymer, the average surface roughness Ra of the plating layer side interface in contact with the electroless copper plating layer 2 is preferably 20 to 150 nm. Furthermore, in particular, when the resin film 1 is a modified polyimide (MPI), the average surface roughness Ra of the plating layer side interface in contact with the electroless copper plating layer 2 is preferably 1 to 150 nm, more preferably 1 to 50 nm. The reasons for this are as follows:
[0034] That is, in the copper clad laminate of this embodiment, in order to make it suitable for use in high frequency circuit boards as described above, it is desired that the transmission characteristics be high at high frequencies of GHz or higher.
[0035] It is generally known that the higher the frequency of a transmission signal, the more the signal propagates through the conductor surface due to the skin effect, and the rougher the conductor surface, the greater the transmission loss. Therefore, in this embodiment, in order to reduce the influence of the transmission loss due to the skin effect, it is preferable to reduce the average surface roughness Ra of the electroless copper plating layer 2 forming the wiring conductor at the interface with the resin film 1.
[0036] On the other hand, in order to ensure adhesion between metal and resin, it has been widely practiced to obtain an anchor effect by roughening the interface between the electroless copper plating layer 2 and the resin film 1. Thus, in the copper clad laminate of this embodiment, there is a trade-off between roughness (adhesion) and transmission loss between the electroless copper plating layer 2 and the resin film 1. The present inventors have conducted extensive research to achieve a balance between the above-mentioned two properties at a higher level, and have found that in this embodiment, the average surface roughness Ra of the resin film 1 at the plating layer side interface in contact with the electroless copper plating layer 2 is preferably set to 1 nm to 150 nm.
[0037] As a result of continued investigations by the present inventors, it was concluded that when the average surface roughness Ra is less than 1 nm, it is not possible to obtain favorable adhesion between the electroless copper plating layer 2 and the resin film 1. On the other hand, when the average surface roughness Ra exceeds 150 nm, in the case where a wiring conductor is formed on a circuit board using the electroless copper plating layer 2 as described above, there is a possibility that favorable transmission characteristics at high frequencies cannot be obtained due to transmission loss caused by the skin effect.
[0038] In this embodiment, the object is to achieve both reduced roughness (reduced transmission loss) and good adhesion between the electroless copper plating layer 2 and the resin film 1 as described above. A specific adhesive strength between the electroless copper plating layer 2 and the resin film 1 is preferably 4.2 N / cm or more in practical use. Furthermore, the above-mentioned adhesive strength is more preferably 5.0 N / cm or more, and even more preferably 6.4 N / cm or more.
[0039] In this embodiment, in order to ensure the above-mentioned adhesion between the electroless copper plating layer 2 and the resin film 1, it is preferable that the electroless copper plating layer 2 and the resin film 1 further have the following characteristics. 2 is a schematic diagram showing the state of the interface between the resin film 1 and the electroless copper plating layer in the copper clad laminate 10 of this embodiment. and It is preferable to provide a carboxyl group for the following reasons.
[0040] 1, in the copper clad laminate 10 of this embodiment, when an electroless copper plating layer 2 is formed by electroless plating on at least one surface of a resin film 1, it is generally known that metallic palladium, which serves as a nucleus for plating, is provided on the surface of the resin film 1. This metallic palladium may be produced using a palladium catalyst.
[0041] In this embodiment, by providing at least one of a hydroxyl group and a carboxyl group to the surface of the resin film 1, it becomes possible to strengthen the adsorption of metallic palladium onto the surface of the resin film 1. As a result, it becomes possible to improve the adhesion between the resin film 1 and the electroless copper plating layer 2.
[0042] In addition, the hydroxyl group at the interface between the resin film 1 and the electroless copper plating layer 2 and The presence of carboxyl groups can be confirmed by known surface analysis methods, such as Fourier transform infrared spectroscopy (FT-IR), X-ray photoelectron spectroscopy (ESCA), time-of-flight secondary ion mass spectrometry (TOF-SIMS), and other known analytical methods.
[0043] In particular, in this embodiment, it is preferable that, at the interface between the resin film 1 and the electroless copper plating layer 2, analysis of the electroless copper plating layer 2 side by time-of-flight mass spectrometry (TOF-SIMS) shows that the peak intensity at mass 121 is 800 (0.12 amu bin) or more. That is, in this embodiment, the results of analysis by TOF-SIMS show that the compound has a mass of 121 and a hydroxyl group. and It is preferable that a functional group containing a carboxyl group is present at the interface between the resin film 1 and the electroless copper plating layer 2. The functional group having a mass of 121 is preferably represented by either the following structural formula 1 or structural formula 2, with structural formula 1 being particularly preferable.
[0044] <Structural formula 1> JPEG2025022881000002.jpg6182
[0045] <Structural formula 2> JPEG2025022881000003.jpg4582
[0046] The "functional group containing a hydroxyl group and / or a carboxyl group" provided at the interface between the resin film 1 and the electroless copper plating layer 2 is not limited to those described above. In addition, if a "functional group containing a hydroxyl group" is provided, a "functional group containing a carboxyl group" does not have to be provided. The reverse is also possible. Furthermore, both a "functional group containing a hydroxyl group" and a "functional group containing a carboxyl group" may be provided.
[0047] In particular, in this embodiment, it is preferable that more "hydroxyl-containing functional groups" than "carboxyl-containing functional groups" are provided at the interface between the resin film 1 and the electroless copper plating layer 2. Alternatively, it is preferable that the interface is provided with "hydroxyl-containing functional groups" and no "carboxyl-containing functional groups."
[0048] 5, the copper clad laminate of this embodiment may further include an electrolytic copper plating layer 4 formed on the above-mentioned electroless copper plating layer 2. That is, when a flexible circuit board is produced by a semi-additive method, it is also possible to further form an electrolytic plating layer on the electroless copper plating layer 2 using the electroless copper plating layer 2 as a seed layer.
[0049] The method for forming a flexible circuit board using the copper clad laminate of this embodiment is not limited to the semi-additive method described above, and other known methods can be applied.
[0050] In the copper clad laminate of this embodiment, it is preferable that electroless copper plating layers are formed on both sides of the resin film, and that through holes H are formed as shown in Fig. 3. That is, it is preferable that the resin film 1 has a through hole in its cross section, and that the through holes H are formed so that at least a part of the electroless copper plating layer 2 covers the inner surface of the through hole. Forming such through holes H is preferable when the copper clad laminate of this embodiment is used for flexible circuit board applications. The position, size, etc. of the through-hole H can be appropriately determined depending on the flexible circuit board to be manufactured, so a detailed description thereof will be omitted.
[0051] The copper clad laminate in this embodiment includes the resin film 1 and the electroless copper plating layer 2 as described above, and may further include a known protective layer formed on the surface of the electroless copper plating layer 2 (the side opposite to the resin film 1) to prevent oxidation of the electroless copper plating layer 2. The protection of the electroless copper plating layer 2 is intended to suppress oxidation, and is formed by carrying out an anti-rust treatment by a known method.
[0052] <Method of manufacturing copper clad laminate> Next, a method for producing the copper clad laminate 10 of this embodiment will be described with reference to FIG. In the present embodiment, the copper clad laminate 10 is produced by forming a carboxyl group on at least one surface of the resin film 1. and A first surface modification step (step 1) of adding hydroxyl groups, and a second surface modification step (step 2) of adding carboxyl groups and The method includes a second surface modification step (step 2) of applying an electric charge to the surface to which hydroxyl groups have been applied by a wet method, a catalyst adsorption step (step 3) of adsorbing a catalyst to the surface to which the electric charge has been applied, an electroless copper plating step (step 4) of forming an electroless copper plating layer 2 on the surface to which the catalyst has been adsorbed, and a heating step (step 5) of heating the copper clad laminate on which the electroless copper plating layer has been formed.
[0053] First, the first surface modification step (step 1) will be described. As described above, the resin film 1 used is preferably a so-called low dielectric resin film. As specific electrical properties of the resin film 1, it is preferable that the relative dielectric constant at a frequency of 10 GHz is 3.5 or less and the dielectric loss tangent is 0.008 or less.
[0054] In the first surface modification step of this embodiment, a carboxyl group is added to at least one surface of the resin film 1. and A hydroxyl group is added. This carboxyl group and As a method for providing hydroxyl groups, a method in which a mixed liquid of an alkaline aqueous solution and an amino alcohol is brought into contact with at least one surface of the resin film 1 can be mentioned.
[0055] The aqueous alkali solution used in the first surface modification step may be either an inorganic alkali or an organic alkali. Examples of inorganic alkali include alkali metal hydroxides such as sodium hydroxide and potassium hydroxide, or carbonates thereof. Examples of organic alkali include tetraalkylammonium hydroxide. The above alkalis may be used alone or in combination.
[0056] On the other hand, the amino alcohol used in the first surface modification step may be specifically an aliphatic amino alcohol or an aromatic amino alcohol, or a derivative thereof.
[0057] Specific examples of amino alcohols that can be used include ethanolamine, heptaminol, isoethanolamine, butanolamine, propanolamine, sphingosine, methanolamine, dimethylethanolamine, and N-methylethanolamine. Of these, it is particularly preferable to use aminoethanol.
[0058] The mixing ratio of the alkaline aqueous solution and amino alcohol in the mixed solution in the first surface modification step is preferably adjusted so that the molar ratio of -OH groups to -NH2 groups (-NH2 groups / -OH groups) is 2.00 to 3.00. By setting the molar ratio within the above range, it is possible to achieve both reduced roughness (reduced transmission loss) and good adhesion between the electroless copper plating layer 2 and the resin film 1, which is an object of the present invention. The reason for this is not clear at present, but the inventors have investigated the matter and presumed it to be due to the following reasons.
[0059] That is, when the first surface modification step is performed on the resin film 1 using the above-mentioned resin with low dielectric loss (such as liquid crystal polymer or modified polyimide resin) with a mixed solution having a molar ratio of (-NH2 group / -OH group) within the above range, it is considered that the state of the surface of the resin film 1 can be such that the average surface roughness Ra of the surface on the electroless copper plating layer 2 side is 1 nm to 150 nm. Therefore, when a wiring conductor is formed on a circuit board using the electroless copper plating layer, the transmission loss due to the skin effect is suppressed, and it becomes possible to exhibit preferable transmission characteristics. In addition, if the average surface roughness Ra of the surface on the electroless copper plating layer 2 side is within the range of 1 nm to 150 nm, the adhesion between the resin film 1 and the electroless copper plating layer 2 can be ensured. Therefore, the present inventors have arrived at the idea of achieving the object of the present invention by carrying out the first surface modification step as described above.
[0060] In addition, by setting the molar ratio of (-NH2 group / -OH group) in the mixed liquid in the first surface modification step within the above range, it is possible to impart more hydroxyl groups than carboxyl groups to the surface of the resin film 1.
[0061] In the first surface modification step, a method for contacting the surface of the resin film 1 with the mixed solution of the alkaline aqueous solution and the amino alcohol can be appropriately applied by a known method, for example, a method of immersing the resin film 1 in the mixed solution, a method of spraying the mixed solution onto the resin film 1 with a spray, etc., etc. are not limited to these methods, and a method of forming a carboxyl group on the surface of the resin film 1 can be used. and Any method other than the above-mentioned methods may be used as long as it is capable of imparting a hydroxyl group.
[0062] In the first surface modification step, the deposition property and adhesion of plating can be improved by adjusting the contact angle of the film surface. In particular, when the resin film 1 is a liquid crystal polymer, the contact angle at the interface on the plating layer side that contacts the electroless copper plating layer 2 is preferably 30° or less. In particular, when the resin film 1 is a modified polyimide (MPI), the contact angle at the interface on the plating layer side that contacts the electroless copper plating layer 2 is preferably 45° or less.
[0063] Next, the second surface modification step (Step 2) of this embodiment will be described. The second surface modification step in this embodiment is preferably a step carried out after the above-mentioned first surface modification step. The second surface modification step is a step of modifying the surface of the resin film 1 by forming a carboxyl group on the surface of the resin film 1 in the first surface modification step. and This is a step of further imparting an electric charge after imparting hydroxyl groups. The imparting of an electric charge is preferable because it makes it possible to improve the adhesion between the resin film 1 and the electroless copper plating layer 2.
[0064] That is, as described above, in order to form the electroless copper plating layer 2, it is preferable that metallic palladium, which serves as a nucleus for plating growth, is present on the resin film 1. In order for this metallic palladium to adhere firmly to the resin film 1, it is preferable that the surface of the resin film 1 has at least a negative charge.
[0065] Preferably, the second surface modification step of this embodiment further includes a step of applying a positive charge to the surface of the resin film 1, and a step of applying a negative charge to the surface to which the positive charge has been applied. By going through these steps, it becomes possible to reliably attach a negative charge to the surface of the resin film 1, which is preferable from the viewpoints of the attachment of the above-mentioned metallic palladium and the adhesion of the electroless copper plating layer 2.
[0066] In the above-mentioned step of providing a positive charge on the surface of the resin film 1, a specific method is to provide a carboxyl group on the surface. and It is possible to further apply a method of immersing the resin film 1 after the addition of hydroxyl groups in a known cationic surfactant, or a method of contacting the resin film 1 with a known cationic surfactant by spraying.
[0067] Similarly, in the step of adsorbing negative charges onto the surface of the resin film 1, a method of immersing in a known anionic surfactant, a method of spraying, or the like can be applied. In addition, the second surface modification step of the present embodiment is preferably performed by a wet method as described above. Performing the process by a wet method has the advantage that it is suitable for mass production by reel-to-reel or the like and can reduce costs.
[0068] Next, the catalyst adsorption step (Step 3) in the production method of this embodiment will be described. The catalyst adsorption step of this embodiment is a step of further adsorbing a catalyst onto the surface of the resin film 1, to which at least a negative charge has been imparted by the above-mentioned second surface modification step.
[0069] In the catalyst adsorption step, a catalyst can be further adsorbed on the surface of the resin film 1 by, for example, contacting a known catalyst liquid with the surface of the resin film 1 by a known method. Examples of the catalyst that can be used include Cu, Ni, Pd, and Ag. Examples of the known catalyst liquid that can be used include, but are not limited to, tin-palladium-based or palladium colloid-based catalyst liquids.
[0070] In the catalyst adsorption step, the amount of catalyst applied to the resin film 1 is 15 μg / dm 2 Regarding the lower limit of the catalyst, the lower the amount, the better, taking into consideration the etching during circuit formation. However, it is necessary to add the catalyst to such an extent that the electroless copper plating layer is well formed, and the lower limit is 1 μg / dm 2 More than this is preferable. If the amount of metallic palladium applied to the resin film 1 exceeds the above-mentioned value, this is not preferable because it may result in a decrease in the reliability of insulation between circuits when the film is made into a flexible circuit board. The amount of metallic palladium can be measured by a known measurement method, for example, by removing only copper from the resin film 1, dissolving the palladium residue on the resin film 1 with nitric acid, and measuring the amount of the residue by ICP.
[0071] Next, the electroless copper plating step (Step 4) in the manufacturing method of this embodiment will be described. The electroless copper plating step is preferably carried out after the catalyst adsorption step. An example of the electroless plating conditions in this embodiment is given below. [An example of electroless copper plating conditions] Bath composition: Copper sulfate 5~10g / L Nickel sulfate 0.5~1.0g / L Rochelle salt 10~30g / L Sodium hydroxide 3~8g / L pH: 7~13 Bath temperature: 29~35℃
[0072] The immersion time of the resin film 1 in the plating bath may be appropriately determined so that the thickness of the electroless copper plating layer 2 becomes 0.1 to 1.0 μm.
[0073] The plating layer formed in this electroless copper plating process is not limited to a plating of simple Cu, but may be a copper alloy plating, such as a Cu-Ni alloy, a Cu-Zn alloy, or a Cu-Sn alloy. In this case, a known plating bath can be appropriately used as the plating bath.
[0074] In the manufacturing method of this embodiment, after forming the electroless copper plating layer 2 on the resin film 1, it is preferable to have a heating step (step 5) in which the entire copper clad laminate on which the electroless copper plating layer has been formed is heated for the purpose of releasing internal stress in the electroless copper plating layer or causing a transformation in the structure. The heating temperature for stress relaxation is preferably 100 to 200° C., and more preferably 120 to 150° C. The heating time for stress relaxation is preferably 5 to 60 minutes, and more preferably 10 to 30 minutes. The heating temperature for transforming the structure is preferably 150 to 350° C., and more preferably 150 to 300° C. The heating time for transforming the structure is preferably 5 to 180 minutes, and more preferably 10 to 30 minutes. The heating atmosphere may be, for example, air or an inert gas atmosphere such as nitrogen. By carrying out the heating step, it is possible to suppress peeling of the electroless copper plating layer 2 from the resin film 1, and also to ensure adhesion between the electroless copper plating layer 2 and the resin film 1. Furthermore, the growth of crystallites in the electroless copper plating layer 2 can improve adhesion between the copper plating layer (electroless copper plating layer 2 and electrolytic copper plating layer 4) and the resin film 1 after laminating the electrolytic copper plating layer 4 described below.
[0075] The method for producing a copper clad laminate of this embodiment may include an electrolytic copper plating step in which, after the formation of the electroless copper plating layer 2 by the electroless copper plating step, an electrolytic copper plating step is performed to form an electrolytic copper plating layer 4 by the electrolytic plating step. As the electrolytic copper plating step, a known copper sulfate bath or copper pyrophosphate bath can be used, and the electrolytic plating conditions (pH, temperature, current density, immersion time, etc.) can be appropriately selected based on the thickness of the electrolytic plating layer, etc. Through the above steps, the copper clad laminate 20 of this embodiment is manufactured.
[0076] In the manufacturing method of this embodiment, the above-mentioned step 5 may be performed by heating (annealing) the entire copper clad laminate after forming the electrolytic copper plating layer 4 on the resin film 1 (i.e., after the electroless copper plating layer and the electrolytic copper plating bath are formed). In other words, in this embodiment, the above-mentioned heating step may be performed after forming the electrolytic copper plating layer 4 on the resin film 1, or a heating step of heating the entire copper clad laminate may be performed after forming the electroless copper plating layer 2 on the resin film 1 and before forming the electrolytic copper plating layer 4. In addition, when the above-mentioned step 5 is performed before forming the electrolytic copper plating layer 4, it is more preferable to perform it before the resist patterning step described below.
[0077] <Flexible circuit board> Next, the flexible circuit board of this embodiment will be described. The flexible circuit board in this embodiment is preferably a flexible circuit board in which a circuit is formed by the electroless copper plating layer 2 of the copper clad laminate 10 described above. As described above, the copper clad laminate 10 of this embodiment has a surface roughness Ra between the resin film 1 and the electroless copper plating layer 2 that is equal to or less than a predetermined value, making it possible to suppress transmission loss as a flexible circuit board. Furthermore, since it is possible to improve the adhesion between the resin film 1 and the electroless copper plating layer 2, it is preferable because even when a semi-additive method is employed, it becomes possible to form a fine circuit pattern.
[0078] More specifically, for example, in the case of the SAP method or MSAP method, the method for manufacturing a flexible circuit board in this embodiment includes, after the above-mentioned steps 1 to 5 (see also FIG. 4), a known resist patterning step of applying and patterning a resist on the electroless plating layer 2, and then the above-mentioned electrolytic copper plating step, whereby an electrolytic plating layer 4 is formed between the patterned resist. The method for forming the flexible circuit board of this embodiment is not limited to the semi-additive method described above, and other known methods such as a full-additive method or a subtractive method can also be used. EXAMPLES
[0079] Next, the present invention will be described more specifically with reference to examples.
[0080] <Example 1> First, a liquid crystal polymer film (Vexstar CTQLCP, manufactured by Kuraray Co., Ltd., thickness: 50 μm) was prepared as the resin film 1. As for electrical properties, the relative dielectric constant at 10 GHz was 3.3, and the dielectric loss tangent at 10 GHz was 0.002.
[0081] Next, as the first surface modification step, both sides of the prepared resin film 1 were immersed in a mixed solution of potassium hydroxide aqueous solution and monoethanolamine for 5 minutes to introduce carboxyl groups and / or hydroxyl groups to both surfaces, and then immersion washing was performed. The temperature of the mixed solution used was 30°C, and the molar ratio of -OH groups to -NH2 groups (-NH2 groups / -OH groups) was 2.29. The peak intensity of mass 121 in TOF-SIMS was 1000.
[0082] Next, as a second surface modification step, both sides of the resin film 1 were immersed in an aqueous solution of 10 g / L of a cationic surfactant for 2 minutes to adsorb positive charges. After immersion and rinsing with water, the film was immersed in an aqueous solution of 3 g / L of an anionic surfactant for 1 minute. In this way, the film was allowed to adsorb positive charges and then negative charges. Furthermore, as the catalyst adsorption process and the electroless copper plating process, the plate was immersed in an aqueous solution of palladium chloride (PdCl2) (2 g / L, pH 12, 40°C) as a plating catalyst for 5 minutes, followed by immersion and water rinsing. Furthermore, the plate was immersed in an aqueous solution (25°C) containing 1 g / L of dimethylamine borane (DMAB) and 6 g / L of boric acid as a catalyst activator (reducing agent) for 5 minutes, followed by immersion and water rinsing. Thereafter, an electroless Cu-Ni plating layer was formed to a thickness of 0.3 μm using an electroless plating bath. The electroless plating conditions were as follows. The Ni content in the resulting electroless Cu-Ni plating layer was determined using the above-mentioned plasma emission spectrometer (ICP) and was found to be 1.18 wt%.
[0083] [Electroless plating conditions] Bath composition: Copper sulfate 7.5g / L Nickel sulfate 0.7g / L Rochelle salt 20g / L Sodium hydroxide 5g / L pH:9 Bath temperature: 32℃
[0084] Thereafter, an electrolytic copper plating layer was formed to a thickness of 18 μm on the electroless Cu—Ni plating layer of the copper clad laminate using an electrolytic plating bath. The electrolytic copper plating conditions were as follows. Bath composition: 200 g / L of copper sulfate hexahydrate 50 g / L of sulfuric acid 50 ppm of chloride ions 5 ml / L of brightener (Additive Top Tinier manufactured by Okuno Pharmaceutical Co., Ltd.) Bath temperature: 20 - 25 °C pH: 1 or less Current density: 2 - 3 A / dm 2
[0085] [Heating (annealing) treatment] In this example, after forming the electroless copper plating layer, the first heat treatment was performed under the following heating conditions, and after forming the electrolytic copper plating layer, the second heat treatment was performed under the following heating conditions. <Heating conditions in the first heat treatment> Heating temperature: 150 °C Heating time: 10 minutes Heating atmosphere: in air <Heating conditions in the second heat treatment> Heating temperature: 230 °C Heating time: 10 minutes Heating atmosphere: in air By going through the above steps, the copper-clad laminate 10 in Example 1 was obtained.
[0086] [Evaluation] <TOF-SIMS and ESCA> In order to confirm the presence of carboxyl groups and / or hydroxyl groups at the interface between the resin film 1 and the electroless copper plating layer 2, the surface state was confirmed. First, the obtained copper clad laminate 10 was immersed in a 42 Baume FeCl3 solution (50°C) without heat treatment, and the electroless copper plating layer 2 was removed when it was visually confirmed that the electroless copper plating layer 2 had disappeared, thereby peeling off the electroless copper plating layer 2 and exposing the resin film. The exposed resin film surface was cut into a size of 20 mm x 20 mm to prepare a measurement sample. This measurement sample was measured with an X-ray photoelectron spectrometer (JPS-9200, manufactured by JEOL Ltd., X-ray source: Mg, analysis area: φ3 mm) to obtain a C1s spectrum. Then, the intensity of the peak derived from the carboxyl group (COO(H) bond) appearing at a binding energy of 288.8 eV and the intensity of the peak derived from the C-C bond appearing at a binding energy of 284.7 eV were calculated.
[0087] According to the ESCA measurement results, the presence of carboxyl groups could not be confirmed. Next, the surface condition of the measurement sample was confirmed by TOF-SIMS.
[0088] The surface of the above measurement sample was analyzed by TOF-SIMS TRIFT-II (manufactured by ULVAC-PHI, Inc.). An untreated resin film sample was used as a control. The measurement conditions were as follows. Primary ion: 69 Ga Acceleration voltage: 15 kV Measurement range: 100μm×100μm Mass range: 0.5 to 300 (m / z)
[0089] The obtained results were analyzed using analysis software Win Cadence (Physical Electronics). It was confirmed that a peak characteristic of mass 121 was observed only on the surface of the sample from which the electroless copper plating had been peeled off in the TOF-SIMS spectrum. No peak characteristic of mass 121 was observed on the surface of the untreated sample. According to the results of ESCA, the presence of carboxyl groups could not be confirmed, and therefore it was determined that C8H9O (-CH-CH3-C6H4-OH) groups were introduced after the first and second surface modification processes.
[0090] <Ra after plating layer peeling> The electroless copper plating layer 2 of the obtained copper clad laminate 10 (electroless copper plating layer thickness: 0.3 μm (Examples 1 to 5, Example 11, and Comparative Examples 1 to 8) or 0.2 μm (Examples 6 to 10 and Comparative Example 9)) was peeled off using an FeCl3 solution in the same manner as described above to expose the resin film. The surface roughness (Ra) of the exposed resin film was measured using a laser microscope (Olympus OLS3500) in AFM mode with a viewing angle of 5 μm × 5 μm. The obtained values are shown in Table 2.
[0091] <Contact angle> The electroless copper plating layer 2 of the obtained copper clad laminate 10 was peeled off using an FeCl3 solution in the same manner as described above to expose the resin film. The exposed resin film surface was cut into a size of 20 mm x 20 mm to prepare a measurement sample. 2.0 μL of pure water was dropped onto the sample surface, and the contact angle was measured using a contact angle measuring device (DropMaster, manufactured by Kyowa Interface Science Co., Ltd.). The contact angle of the untreated resin surface used in Example 1 was 65°, and the contact angle of the untreated resin surface used in Example 5 was 58°.
[0092] <Tape peel strength> A tape peel test was performed on the surface of the electroless copper plating layer 2 of the obtained copper clad laminate 10 (thickness of the electroless copper plating layer: 0.3 μm (in the cases of Examples 1 to 5, Example 11, and Comparative Examples 1 to 8) or 0.2 μm (in the cases of Examples 6 to 10 and Comparative Example 9)) by applying an adhesive tape (manufactured by Nichiban Co., Ltd.) to the surface of the electroless copper plating layer 2 and then peeling it off. If peeling of the electroless copper plating layer 2 was not confirmed by visual inspection, the evaluation result was rated as good. The results are shown in Table 2.
[0093] <90°Peel strength> After the electrolytic copper plating was formed and the copper clad laminate 20 was subjected to a second heat treatment at 230° C. for 10 minutes, a test piece measuring 40 mm×40 mm was cut out, and the test piece was attached to an aluminum plate with polyimide tape. The 90° peel strength was measured as the adhesive strength between the resin film and the electroless copper plating layer as follows.
[0094] That is, on the surface on which the electrolytic copper plating layer was formed on each test material, rectangular cuts were made with a cutter at intervals of 5 mm on the copper plating surface, and then the ends of the rectangular cuts were forcibly peeled off to trigger the peeling, creating a peeled resin film and copper plating part. Next, the peeled resin film and copper plating layer were clamped with a Tensilon chuck, and the 90° peel strength was measured by autograph. The 90° peel strength was converted to N / cm (width). The results are shown in Table 2.
[0095] <Platability (visual inspection)> The appearance of the electroless copper plating layer of the obtained copper clad laminate was visually observed. Those without peeling or blistering were marked with "O" and shown in Table 2.
[0096] <Measurement of Ni content in electroless copper plating layer 2> After forming the electroless copper plating layer 2 under the conditions shown in Table 1, an area of 2 cm x 2 cm was immersed in 30% nitric acid (at room temperature) to dissolve the electroless copper plating layer 2. The weights of Cu (copper) and Ni (nickel) in the resulting liquid were measured using a plasma emission spectrometer (ICP) (Shimadzu Corporation ICPE-9820), and the Ni weight / Cu weight+Ni weight was calculated to calculate the Ni content of the electroless copper plating layer 2.
[0097] <Overall rating> The above evaluation items were comprehensively judged, and the results are shown in Table 2, with ◯ for items that were acceptable for practical use and × for items that were not practical.
[0098] <Example 2> The same procedure as in Example 1 was carried out, except that the temperature of the mixed liquid in the first surface modification step was changed to the temperature shown in Table 1. The results are shown in Tables 1 and 2.
[0099] <Example 3> The same procedure as in Example 1 was carried out, except that the molar ratio of -OH groups to -NH2 groups (-NH2 groups / -OH groups) in the mixed liquid in the first surface modification step was changed to the values shown in Table 1. The results are shown in Tables 1 and 2.
[0100] <Example 4> The same procedure as in Example 1 was carried out, except that the temperature of the mixed liquid in the first surface modification step was changed to the temperature shown in Table 1. The results are shown in Tables 1 and 2.
[0101] <Example 5> A modified polyimide (MPI) resin (FS-L manufactured by SKC Kolon PI, thickness: 50 μm) was prepared as the resin film 1. As for the electrical properties, the relative dielectric constant at 10 GHz was 3.4, and the dielectric loss tangent at 10 GHz was 0.0035.
[0102] Next, as the first surface modification step, both sides of the prepared resin film 1 were immersed in a mixed solution of sodium hydroxide aqueous solution and monoethanolamine for 5 minutes to introduce carboxyl groups and / or hydroxyl groups to both surfaces, and then immersion washing was performed. The temperature of the mixed solution used here was 40°C, and the molar ratio of -OH groups to -NH2 groups (-NH2 groups / -OH groups) was 0.19.
[0103] Next, as a second surface modification step, a positive charge was absorbed on both sides of the resin film 1 by the same method as in Example 1, and then a negative charge was absorbed on both sides. Furthermore, as the catalyst adsorption process and the electroless copper plating process, the plate was immersed in an aqueous solution (2 g / L, pH 12, 40°C) of palladium chloride (PdCl2) as a plating catalyst for 5 minutes, followed by immersion and washing with water. Furthermore, the plate was immersed in an aqueous solution (25°C) containing 1 g / L of dimethylamine borane (DMAB) and 6 g / L of boric acid as a catalyst activator (reducing agent) for 5 minutes, followed by immersion and washing with water.
[0104] Thereafter, an electroless Cu-Ni plating layer was formed to a thickness of 0.3 μm in an electroless plating bath under the following electroless plating conditions: The Ni content in the electroless Cu-Ni plating layer was 1.18 wt %. [Electroless plating conditions] Bath composition: Copper sulfate 7.5g / L Nickel sulfate 0.7g / L Rochelle salt 20g / L Sodium hydroxide 5g / L pH: 12.5 Temperature: 32℃ Processing time: 10 minutes
[0105] Thereafter, in the same manner as in Example 1, an electrolytic copper plating layer was further formed to a thickness of 18 μm on the electroless Cu—Ni plating layer of the copper clad laminate using an electrolytic plating bath.
[0106] [Heat (annealing) treatment] In Example 5, after forming the electroless copper plating layer, a first heating treatment was performed using a dry oven (DY300 manufactured by Yamato Scientific Co., Ltd.) under the following heating conditions: The second heating treatment after the electrolytic plating described above was omitted. <Heating conditions in the first heat treatment> Heating temperature: 150℃ Cooking time: 60 minutes Heating atmosphere: Air By going through the above steps, the copper clad laminate 10 of Example 5 was obtained. In this manner, the copper clad laminate 10 of Example 5 was obtained, and this copper clad laminate was evaluated in the same manner as in Example 1. The results of Example 5 are shown in Tables 1 and 2.
[0107] <Example 6> A copper clad laminate was obtained in the same manner as in Example 2, except that the plating thickness of the electroless Cu-Ni plating layer was 0.2 μm, annealing (heat treatment) was performed in an inert (nitrogen) gas at 280° C. for 180 minutes using a vacuum drying device (DQ-46P-LP manufactured by Sato Vacuum Co., Ltd.), and this annealing (heat treatment) was performed after the electroless copper plating and before the electrolytic copper plating. Note that no heat treatment was performed after the electrolytic copper plating. The copper clad laminate of Example 6 was evaluated in the same manner as in Example 1. The results of Example 6 are shown in Tables 1 and 2.
[0108] <Example 7> A copper clad laminate was obtained in the same manner as in Example 6, except that the content of nickel sulfate in the electroless Cu-Ni plating bath was 0.32 g / L. The Ni content in the obtained electroless Cu-Ni plating layer was 0.74 wt%. The copper clad laminate of Example 7 was evaluated in the same manner as in Example 1. The results of Example 7 are shown in Tables 1 and 2.
[0109] <Example 8> A copper clad laminate was obtained in the same manner as in Example 6, except that the content of nickel sulfate in the electroless Cu-Ni plating bath was 0.13 g / L. The Ni content in the obtained electroless Cu-Ni plating layer was 0.41 wt%. The copper clad laminate of Example 8 was evaluated in the same manner as in Example 1. The results of Example 8 are shown in Tables 1 and 2.
[0110] <Example 9> A copper clad laminate was obtained in the same manner as in Example 6, except that the content of nickel sulfate in the electroless Cu-Ni plating bath was 0.065 g / L. The Ni content in the obtained electroless Cu-Ni plating layer was 0.18 wt%. The copper clad laminate of Example 9 was evaluated in the same manner as in Example 1. The results of Example 9 are shown in Tables 1 and 2.
[0111] <Example 10> A copper clad laminate was obtained in the same manner as in Example 6, except that the content of nickel sulfate in the electroless Cu-Ni plating bath was 0.013 g / L. The Ni content in the obtained electroless Cu-Ni plating layer was 0.14 wt%. The copper clad laminate of Example 10 was evaluated in the same manner as in Example 1. The results of Example 10 are shown in Tables 1 and 2.
[0112] <Example 11> A copper clad laminate was obtained in the same manner as in Example 6, except that the content of nickel sulfate in the electroless Cu-Ni plating bath was 0.0065 g / L and the thickness of the electroless Cu-Ni plating layer was 0.3 μm. The Ni content in the obtained electroless Cu-Ni plating layer was 0.09 wt%. The copper clad laminate of Example 11 was evaluated in the same manner as in Example 1. The results of Example 11 are shown in Tables 1 and 2.
[0113] <Comparative Example 1> First, a polyimide film (Kapton, manufactured by DuPont-Toray Co., Ltd., thickness: 50 μm) was prepared as the resin film 1. As for the electrical properties, the relative dielectric constant at 1 MHz was 3.4, and the dielectric loss tangent at 1 MHz was 0.0024. Next, the prepared resin film 1 was immersed in an aqueous potassium hydroxide solution (200 g / L) at 30° C. for 10 minutes, and then immersed and rinsed with water.
[0114] In the catalyst adsorption step and the electroless plating step, the plating catalyst was immersed in an aqueous solution of palladium chloride (PdCl2), then in an aqueous solution of dimethylamine borane (DMAB) as a catalyst activator (reducing agent), and after immersion and rinsing with water, an electroless nickel-phosphorus plating layer of 0.5 μm was formed in an electroless nickel-phosphorus plating bath. The electroless plating conditions were as follows. The conditions for the catalyst adsorption step were the same as those in Example 1. The subsequent electrolytic copper plating and annealing (heat treatment) were the same as those in Example 1.
[0115] [Electroless plating conditions] Bath composition: Nickel sulfate 27g / L Sodium hypophosphite 30g / L Malic acid 30g / L Lactic acid 15g / L Stabilizer 0.6ppm pH: 4.5 Temperature: 89℃ Processing time: 5 minutes
[0116] <Comparative Example 2> The same procedure as in Comparative Example 1 was carried out, except that the resin film used was the liquid crystal polymer film used in Example 1. The results are shown in Tables 1 and 2.
[0117] <Comparative Example 3> The same procedure as in Comparative Example 2 was carried out, except that the electroless plating layer was an electroless copper plating layer. [Electroless plating conditions] Bath composition: Copper sulfate 6g / L Rochelle salt 20g / L Formalin 5g / L pH: 11.5 Temperature: 30℃ Processing time: 10 minutes
[0118] <Comparative Example 4> The same procedure as in Comparative Example 3 was carried out, except that the second surface modification step was carried out under the same conditions as in Example 1.
[0119] <Comparative Example 5> The same procedure as in Example 1 was carried out, except that the molar ratio of -OH groups to -NH2 groups (-NH2 groups / -OH groups) in the mixed liquid used in the first surface modification step was 0.23.
[0120] <Comparative Example 6> The first surface modification step was carried out in the same manner as in Example 1, except that the molar ratio of -OH groups to -NH2 groups (-NH2 groups / -OH groups) in the mixed liquid used was 0.45.
[0121] <Comparative Example 7> The same procedure as in Example 1 was carried out, except that the molar ratio of -OH groups to -NH2 groups (-NH2 groups / -OH groups) in the mixed liquid used in the first surface modification step was set to 0.92.
[0122] <Comparative Example 8> The same procedure as in Example 1 was carried out, except that the mixed solution used in the first surface modification step had a molar ratio of -OH groups to -NH2 groups (-NH2 groups / -OH groups) of 1.83.
[0123] <Comparative Example 9> The same procedure was followed as in Example 2, except that the electroless plating formed on the resin film was copper plating (Ni content was 0), the plating thickness of this electroless Cu plating was 0.2 μm using the same plating solution as in Comparative Example 3, annealing (heat treatment) was performed in an inert (nitrogen) gas at 280° C. for 180 minutes using the same device as in Example 6, and this annealing (heat treatment) was performed after the electroless copper plating and before the electrolytic copper plating. In Comparative Example 9, since the electroless Cu plating layer was locally unplated, electrolytic Cu plating was performed only on the area where the electroless Cu plating layer was formed, and evaluations other than the measurement of peel strength were performed.
[0124] [Table 1]
[0125] [Table 2] [Industrial Applicability]
[0126] Since the surface roughness Ra between the resin film and the electroless copper plating layer of the copper clad laminate of the present invention is equal to or less than a predetermined value, it is possible to suppress the transmission loss as a flexible circuit board and provide high transmission characteristics at high frequencies. In addition, since it is possible to improve the adhesion between the resin film and the electroless copper plating layer, it is possible to form a fine circuit pattern even when a full-additive method or a semi-additive method is adopted as a method for forming a circuit. It is clear that the copper clad laminate of the present invention is suitably applied to wiring boards and the like which require fine wiring of a multi-layer structure. [Explanation of symbols]
[0127] 1 Resin film 2. Electroless copper plating layer 4 Electrolytic plating layer 10 Copper clad laminate 20 Copper clad laminate
Claims
1. a low dielectric resin film having a relative dielectric constant of 3.5 or less and a dielectric tangent of 0.008 or less at a frequency of 10 GHz; an electroless copper plating layer laminated on at least one surface of the low dielectric resin film; Including, The electroless copper plating layer is an electroless Cu-Ni alloy plating layer, the low dielectric resin film has an average surface roughness Ra of 1 to 150 nm at a plating layer side interface in contact with the electroless Cu—Ni alloy plating layer, and the 90° peel strength between the resin film and the electroless Cu—Ni alloy plating layer is 4.2 N / cm or more; a plating layer side interface of the resin film is provided with hydroxyl groups, and the number of hydroxyl groups at the plating layer side interface is greater than the number of carboxyl groups; A copper clad laminate, characterized in that the peak intensity at mass number 121 in a TOF-SIMS spectrum of the plating layer side interface is 1000 or more.
2. 2. The copper clad laminate according to claim 1, wherein the intensity of mass 121 at the interface of the resin film on the plating layer side by time-of-flight mass spectrometry (TOF-SIMS) is 800 or more.
3. 3. The copper clad laminate according to claim 1, wherein the resin film is any one of polyimide, modified polyimide, liquid crystal polymer, fluorine-based resin, or a mixture thereof.
4. A copper clad laminate described in any one of claims 1 to 3, wherein the Ni content in the electroless Cu-Ni alloy plating layer is 3 wt% or less.
5. The copper clad laminate according to any one of claims 1 to 4, wherein the electroless Cu-Ni alloy plating layer has a thickness in the range of 0.1 to 1.0 µm.
6. The copper clad laminate according to any one of claims 1 to 5, wherein a metal consisting of any one of Cu, Ni, Pd, and Ag is present at the interface of the resin film on the electroless Cu-Ni alloy plating layer side.
7. The copper clad laminate according to any one of claims 1 to 6, further comprising a protective layer formed on the electroless Cu-Ni alloy plating layer.
8. The electroless Cu-Ni alloy plating layer is formed on both sides of the resin film, 8. The copper clad laminate according to claim 1, wherein the resin film has a through hole, and at least a part of the electroless Cu-Ni alloy plating layer is formed on an inner wall of the through hole.
9. A method for producing a copper clad laminate, comprising forming an electroless copper plating layer on a resin film having a relative dielectric constant of 3.5 or less and a dielectric loss tangent of 0.008 or less at a frequency of 10 GHz, a first surface modification step of providing a carboxyl group and a hydroxyl group to the surface of the resin film; a second surface modification step of providing an electric charge to the surface to which the carboxyl group and the hydroxyl group have been provided by a wet method; a catalyst adsorption step of adsorbing a catalyst onto the surface to which the charge has been applied; an electroless copper plating step of forming an electroless Cu-Ni alloy plating layer on the surface on which the catalyst is adsorbed; a heating step of heating the copper clad laminate on which the electroless Cu-Ni alloy plating layer is formed; Including, In the first surface modification step, a mixed solution of an alkaline aqueous solution and an amino alcohol is used, and the mixed ratio in the mixed solution is, in terms of molar ratio, a ratio of —OH groups to —NH 2 groups (—NH 2 groups / —OH groups) of 2.00 to 3.00; The plating layer side interface of the resin film is provided with the hydroxyl group, and A method for producing a copper clad laminate, characterized in that the hydroxyl groups are provided in greater numbers than the carboxyl groups at the plating layer side interface.
10. A method for producing a copper clad laminate by forming an electroless copper plating layer on a modified polyimide (MPI) as a resin film having a relative dielectric constant of 3.5 or less and a dielectric loss tangent of 0.008 or less at a frequency of 10 GHz, comprising: a first surface modification step of providing a carboxyl group and a hydroxyl group to the surface of the resin film using a mixed solution of an alkaline aqueous solution and an amino alcohol; a second surface modification step of providing an electric charge to the surface to which the carboxyl group and the hydroxyl group have been provided by a wet method; a catalyst adsorption step of adsorbing a catalyst onto the surface to which the charge has been applied; an electroless copper plating step of forming an electroless Cu-Ni alloy plating layer on the surface on which the catalyst is adsorbed; a heating step of heating the copper clad laminate on which the electroless Cu-Ni alloy plating layer is formed; Including, A method for producing a copper clad laminate, characterized in that the plating layer side interface of the resin film is provided with hydroxyl groups, and the number of hydroxyl groups at the plating layer side interface is greater than the number of carboxyl groups.
11. The method for producing a copper clad laminate according to claim 9 or 10, wherein the amino alcohol is aminoethanol.
12. The method for producing a copper clad laminate according to any one of claims 9 to 11, wherein in the second surface modification step, a positive charge is adsorbed onto the surface to which the carboxyl group and the hydroxyl group have been added, and then a negative charge is adsorbed onto the surface.
13. The method for producing a copper clad laminate according to claim 12, further comprising adding a cationic surfactant to the surface to adsorb the positive charges and adding an anionic surfactant to the surface to adsorb the negative charges.
14. A flexible circuit board having a circuit formed thereon using the copper clad laminate according to any one of claims 1 to 8.
Citation Information
Patent Citations
Plating method
JP2002256443A
Plating method of resin molded body
JP2007254606A
Plating film-attached resin product, production method thereof and encoder
JP2016113688A
Plating transfer film
JP2017208540A
Datsusuikikabaanorotsukusochi
JP1976086266A